Clinical Spectrum Time Course in Anti Jo-1 Positive Antisynthetase Syndrome. Issue 32 (August 2015) - Cavagna, Lorenzo; Nuño, Laura; Scirè, Carlo Alberto; Govoni, Marcello; Longo, Francisco Javier Lopez; Franceschini, Franco; Neri, Rossella; Castañeda, Santos; Giraldo, Walter Alberto Sifuentes; Caporali, Roberto; Iannone, Florenzo; Fusaro, Enrico; et al.
<x xml:space="preserve">Abstract</x> Abstract Anti Jo-1 antibodies are the main markers of the antisynthetase syndrome (ASSD), an autoimmune disease clinically characterized by the occurrence of arthritis, myositis, and interstitial lung disease (ILD). These manifestations usually co-occur (for practical purpose complete forms) in the same patient, but cases with only 1 or 2 of these findings (for practical purpose incomplete forms) have been described. In incomplete forms, the ex novo occurrence of further manifestations is possible, although with frequencies and timing not still defined. The aim of this international, multicenter, retrospective study was to characterize the clinical time course of anti Jo-1 positive ASSD in a large cohort of patients. Included patients should be anti Jo-1 positive and with at least 1 feature between arthritis, myositis, and ILD. We evaluated the differences between complete and incomplete forms, timing of clinical picture appearance and analyzed factors predicting the appearance of further manifestations in incomplete ASSD. Finally, we collected 225 patients (58 males and 167 females) with a median follow-up of 80 months. At the onset, complete ASSD were 44 and incomplete 181. Patients with incomplete ASSD had frequently only 1 of the classic triad findings (110 cases), in particular, isolated arthritis in 54 cases, isolated myositis in 28 cases, and isolated ILD in 28 cases. At the end of follow-up, complete ASSD were 113, incomplete 112. Only 5 patients had an isolated arthritis, only 5 an isolated myositis, and 15 an isolated ILD. During the follow-up, 108 patients with incomplete forms developed further manifestations. Single main feature onset was the main risk factor for the ex novo appearance of further manifestation. ILD was the prevalent ex novo manifestation (74 cases). In conclusion, ASSD is a condition that should be carefully considered in all patients presenting with arthritis, myositis, and ILD, even when isolated. The ex novo appearance of further manifestations in patients with incomplete forms is common, thus indicating the need for an adequate clinical and instrumental follow-up. Furthermore, the study clearly suggested that in ASSD multidisciplinary approach involving Rheumatology, Neurology, Pneumology, and Internal Medicine specialists is mandatory.